Quality of Life, Psychological Interventions and Treatment Outcome in Tuberculosis Patients: The Indian Scenario - Peddireddy, Vidyullatha (Frontiers in Psychology, 2016)
Objective: Psychological distress is being recognized in individuals affected with many diseases since it affects quality of life and has gained importance in the clinical settings. Psychological interventions and their effect on the treatment outcome has yielded encouraging results in many diseased conditions. Tuberculosis ranks as a deadly disease resulting in millions of deaths worldwide. However, the effect of tuberculosis on the psychological status of patients and interventions to improve treatment outcome is neglected, especially in underdeveloped and developing countries. Methods: Systematic review of research papers that published on the quality of life in tuberculosis and the effect of psychological interventions on treatment outcome was conducted. Results: Tuberculosis patients experience high levels of stress and decreased quality of life. In the Indian scenario, tuberculosis patients undergo immense psychological stress similar to what is reported in other locations. Psychological interventions renewed hope on life and adherence to medication and treatment outcomes. Such psychological interventions are not practiced in Indian clinical settings. Conclusions: There is an urgent need for both governmental and non-governmental organizations to devise strategies to include psychological interventions mandatory during tuberculosis treatments. In the absence of such interventions, the fight against tuberculosis in India will remain incomplete.